"It's not smoke. It's not tar. It's not 4000 chemicals. Case closed": Exploring attitudes, beliefs, and perceived social norms of e-cigarette use among adult users. (1st February 2016) - Coleman, Blair N.; Johnson, Sarah E.; Tessman, Greta K.; Tworek, Cindy; Alexander, Jennifer; Dickinson, Denise M.; Rath, Jessica; Green, Kerry M.
Highlights: Positive attitudes towards e-cigarettes are accompanied by wariness about them. Users reported a lack of knowledge of e-cigarette ingredients and health effects. Many users expressed interest in knowing more about what is in e-cigarette products. Many described positive reactions from friends and family members about their use. Abstract: Background: Electronic cigarette (e-cigarette) use is rapidly increasing among adults in the U.S. The purpose of this qualitative study was to explore consumer perceptions about e-cigarettes, including knowledge, attitudes, beliefs and perceived social norms. Methods: A total of 14 focus groups ( N = 116) were conducted with current adult e-cigarette users in five U.S. cities from March through May, 2014. Focus groups were segmented by age (young adults aged 18–29 and older adults aged 30 and older) as well as by e-cigarette use status (exclusive e-cigarette users and non-exclusive e-cigarette users). Focus group discussions lasted approximately 60-min and were audio-recorded and transcribed; data were analyzed using a phenomenological approach. Results: Participants expressed many positive attitudes towards e-cigarettes and simultaneously reported a lack of information and knowledge about the products. Focus group participants overwhelmingly felt as though the ingredients of e-cigarettes were likely less harmful than conventional cigarettes. Additionally, many described positive reactions from family and friends, especially when e-cigarettes were used in place of conventional cigarettes. Conclusions: Findings from this qualitative study provide insight into consumer knowledge, attitudes and beliefs about e-cigarettes increasing our understanding of why and how they are being used. Such information will help provide insight into the potential public health impact of these emerging products.